Growth, reproductive physiology and spectral characteristics of Bt cotton under biotic and abiotic stresses - Kaur, Ramanjit; Deol, J.S.; Brar, A. S.; Jaidka, Manpreet; Sepat, Seema (Annals of Agricultural Research, 2016)
Field experiment was conducted during Kharif 2010-11 and 2011-12, at the experimental area, Department of Agronomy, Punjab Agricultural University, Ludhiana to study the growth, reproductive physiology and spectral characteristics of Bt Cotton under biotic and abiotic stresses. The results concluded that weed free treatment showed significantly higher cotton yield (127%) over control and it was at par with recommended weed control and irrigation treatment and the treatment where irrigation stress was given at blooming stage. Lowest cotton yield was recorded in control treatment. Comparatively lower yield (18% less than weed free) was recorded in irrigation stress treatments due to decreased optimum moisture availability at critical stages. Normalised difference vegetation index (NDVI) values recorded in treatement, where recommended weed control and irrigation practices were applied (T 1) and in weed free (manual, T2) treatment were higher than all other treatments at all growth stages indicates better crop vigor. In absolute control (no herbicide and no irrigation) treatment, irrigation stress at Blooming stage and irrigation stress at reproductive stage, lower value of NDVI indicates poor health of crop, more leaf senescence due to which more of near infra-red (NIR) light was absorbed by senescent leaves than red light. More absorption of NIR light decreased the value of NDVI.